PPAT'S responsibility for deeds of sale and purchase made in his presence (Study of PPAT in Kupang City) - Jonneri Bukit; Rizky Tuahta Cristian Bukit (Institute Of computer Science (IOCS), 2023)
This research aims to describe the process of the birth of a sale-purchase deed, and find out how the responsibility of a Land Deed Official (PPAT). The research method used in this research is empirical normative research, with primary and secondary data types. The results show that the responsibility of PPAT in making land sale and purchase deeds regarding the form and procedure for making PPAT deeds is not only regulated in Government Regulation of the Republic of Indonesia Number 24 of 2016 concerning Amendments to Government Regulation Number 37 of 1998 concerning PJPPAT Articles 21-24 but also in Government Regulation No. 24 of 1997 concerning Land Registration which regulates this matter is confirmed in Article 38 paragraph (2) which determines